Wie können wir berechnen? (1-x) + (1-x) ^ 2 + (1-x) ^ 3 + (1-x) ^ 4 + (1-x) ^ 5 .... + (1-x) ^ n - Algebra - 2020

Anonim

Antworten:

# ((1 + (1 - x) ^ n) (1-x)) / (x-2) #

Erläuterung:

Die polynomische Identität

#sum_ (k = 0) ^ n a ^ k = (a ^ (n + 1) -1) / (a-1) # lass uns zu

#sum_ (k = 1) ^ n (1-x) ^ k = ((1-x) ^ (n + 1) -1) / ((x-1) -1) -1 = ((1 + ( 1 - x) ^ n) (1-x)) / (x-2) #

Zum #x ne 2 #

Wenn wir stattdessen haben

#sum_ (k = 0) ^ (n-1) (1-x) ^ k = ((1-x) ^ n-1) / ((x-1) -1) = ((1-x) ^ n-1) / (x-2) #

zum #x ne 2 #